The complete mitochondrial genome of the Gymnocypris scleracanthus (Cypriniformes: Cyprinidae) - Chi Zhang; Jing Liu; Wangliang Wang; Jianshe Zhou; Yingzi Pan; Zhenbo Mou (Mitochondrial DNA. Part B. Resources, 2017)
The Gymnocypris scleracanthus, a species of genus Gymnocypris belongs to Schizothoracinaein Cyprinidae. In this study, the complete mitochondrial DNA genome sequence of G. scleracanthus was determined. The 16,771 bp long circular molecule contains 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and two non-coding regions, showing a typical vertebrate pattern. These genes except ND6 and eight tRNA genes were encoded on the H-strand. Phylogenetic analysis showed that the G. scleracanthus was a part of genus Gymnocypris and had closer relationship with Gymnocypris dobula and was independent from other species of Psilorhynchus and Labeoninae in Cyprinidae.